Political Subjects, Activism and Social Subjectivation in Contemporary China: a Tentative Historical Sketch - Chevrier, Yves (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2018)
Rather than using a substantive definition of subjects and examining their relation to politics as an effect of their agency, subjectivation patterns are analyzed in light of the successive modes for producing the political that have spanned the Chinese twentieth century. The rise of the political subject from citizen to social activist is linked to the failed political institution that takes place after empire (part I). In the de-institutionalized context of missing state that ensues, the activist mode of subjectivation takes a violent turn under Maoism (part II), while the present after-revolution is characterized by a social reframing of subjectivations without the long-standing support of political activism (part III). Foucault’s concept of subjectivation is mustered together with Hegel’s own concept of political subjectivation in the context of the French Terror, and with that of the contemporary Chinese philosopher Li Zehou, in order to explain how there were political subjects under Mao’s totalitarian rule, and how there can be social subjects in today’s authoritarian China with no “transition to democracy” in sight. Sujets politiques, activisme et subjectivation sociale dans la Chine contemporaine : essai d’esquisse historique Au lieu d’une approche substantielle des sujets conduisant à étudier leur relation au politique via leur agency, des formes de subjectivation sont analysées en rapport avec les modes de construction du politique qui se succèdent en Chine au long du XXème siècle. De la citoyenneté à l’activisme social, l’essor du sujet politique est lié à l’échec de l’institution politique après la chute de l’empire (partie I). Dans le contexte désinstitutionnalisé d’Etat manquant qui s’ensuit, la subjectivation activiste subit le tournant violent du maoïsme (II). L’actuelle après-révolution se caractérise par le reformatage social des subjectivations, sans le support longtemps prédominant de l’activisme politique (III). La conception foucaldienne de la subjectivation est mise en rapport avec la théorie hégélienne de la subjectivation politique dans la Terreur, ainsi qu’avec celle du philosophe chinois contemporain Li Zehou, afin d’expliquer comment il put y avoir des sujets politiques sous le régime totalitaire de Mao, et comment il y a des sujets sociaux dans la Chine autoritaire d’aujourd’hui en l’absence de « transition démocratique ».